Involvement of Nucleotide-Binding Oligomerization Domain-Like Receptor Family Pyrin Domain Containing 3 Inflammasome in the Pathogenesis of Liver Diseases - Shi, Congjian; Yang, Hongqin; Zhang, Zhenghong (Frontiers in Cell and Developmental Biology, 2020)
The inflammasome is widely acknowledged for its crucial role in the pathogenesis of cancers and many neurodegenerative, metabolic, and auto-inflammatory diseases in recent years. Multiple types of inflammasomes exist. However, nucleotide-binding oligomerization domain-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is the most often investigated inflammasome and has come to limelight in recent studies. NLRP3 inflammasome is a multi-protein complex. Its activation can cause the cleavage of inactive pro-caspase-1 into activated caspase-1, that ultimately promotes the transformation of pro- interleukin (IL)-1β and pro-IL-18 into biologically-active IL-1β and IL-18, respectively. These processes lead to the local inflammatory responses and induce pyroptosis, causing disparaging effects. Recently, numerous studies have shown that NLRP3 inflammasome plays an important role in the pathogenesis of liver diseases, including non-alcoholic fatty liver disease, liver fibrosis, cirrhosis, and hepatocellular carcinoma. Liver diseases have become a severe health burden worldwide, and there is adequate evidence indicating that the regulation of NLRP3 inflammasome acts as a guard against hazard to liver. In this review, we provide a straightforward overview of NLRP3 inflammasome as well as several frequent liver diseases. We then discuss the contribution and regulation of NLRP3 inflammasome during the pathogenesis of liver diseases, which may provide an important indication for the prevention and treatment of various liver diseases.